’’سحر البیان‘‘ کے تنقیدی سرمائے کا تحقیقی و تجزیاتی مطالعہ - Dr. Samina Saif; Dr. Nasima Rehman; Dr. Badshah Malik (Khayaban - خیابان, 2022)
Sehr-ul Bayan, a Masnavi by Meer Hassan, is an account of literary trends and inclinations, internal and external happenings, and the experiences of mind and heart in the Lakhnavi society of 18th century. This Masnavi is a perfect confluence of the poetry of emotions and senses. The style of Sehr-ul Bayan is simple, spontaneous, and mundane. The poet's pen is adept at circumstantiality and representation of culture and civilization. This Masnavi-styled poetic narration also helps in the historical, socio-political, moral and cultural studies. The dissertation writers have covered all the aspects of characterization, style, sexual and psychological issues, as well as spiritual and philosophical problems, while keeping the literary and technical principles in consideration.